Abduction paresis with rostral pontine and/or mesencephalic lesions: Pseudoabducens palsy and its relation to the so-called posterior internuclear ophthalmoplegia of Lutz - Thömke, Frank (BioMed Central, 2001)
BACKGROUND: The existence of a prenuclear abduction paresis is still debated. METHODS: In a retrospective design, we identified 22 patients with isolated unilateral (n = 20) or bilateral (n = 2) abduction paresis and electrophysiologic abnormalities indicating rostral pontine and/or mesencephalic lesions. Another 11 patients had unilateral abduction paresis with additional ocular motor abnormalities indicating midbrain dysfunction. Eight of these 11 patients also had electrophysiological abnormalities supporting this location. Electrophysiological examinations in all patients included masseter and blink reflexes (MassR, BlinkR), brainstem auditory evoked potentials (BAEP), and direct current elctro-oculography (EOG). RESULTS: Unilateral MassR abnormalities in patients with unilateral abduction paresis were seen in 17 patients and were almost always (in 16 of 17 patients) on the side of the abduction paresis. Another 11 patients had bilateral MassR abnormalities. BlinkR was always normal. EOG disclosed slowed abduction saccades in the non-paretic eye in 6 patients and slowed saccades to the side opposite to the abduction paresis in another 5 patients. Re-examinations were done in 27 patients showing normalization or improvement of masseter reflex abnormalities in 18 of 20 patients and in all patients with EOG abnormalities. This was always associated with clinical improvement. CONCLUSIONS: Electrophysiologically documented or clinically evident rostral pontine and/or mesencephalic lesions in our patients exclude an infranuclear intrapontine 6th nerve lesion and indicate the existence of an abduction paresis of prenuclear origin. An increased tone of the antagonistic medial rectus muscle during lateral gaze either by abnormal convergence or impaired medial rectus inhibition seems most likely.